Analysis of Expressed Genes in Normal and Tumoral Mammary Gland Tissue of the Terrier Dog - Ozdemir Ozgenturk, Nehir; Omeroglu Ulu, Zehra; Ulu, Salih; Celik, Merve; Tellioglu, Burcin; Yildirim, Funda; Akis Akad, Iraz; Gurel, Aydin; Un, Cemal; Oztabak, Kemal Ozdem (KAFKAS UNIV, VETERINER FAKULTESI DERGISI, 2018)
Mammary gland tumor is the most common type of tumor in female dogs. Data on genes that are involved in tumorigenesis and mechanism of tumor development are insufficient. Comparative studies have been conducted in order to see if tumorigenesis studies in the dog could be a model for human mammary gland tumors. In this study, we constructed two different cDNA libraries from mammary tissue, which were collected from a normal mammary tissue of a healthy Terrier dog and a tumoral mammary tissue of a sick dog. A total 2304 colonies which are randomly picked out from the two libraries were sequenced for developing a dog mammary gland ESTs collection. Raw EST data were analyzed with Phred/Phrap programs and readable EST sequences were assembled with the CAP3 program. All of EST sequences were grouped into 45 contig and 2203 singletons. Putative functions of all unique sequences were designated by NCBI BLAST based on gene homology and annotated by BLAST2GO. The results of this study are a very valuable resource for functional genome studies of the dogs.
Keywords: Terrier; Dog; Breast cancer; EST; cDNA library; SEQUENCE TAGS; IDENTIFICATION; NEOPLASMS; PROFILES; MODEL; Veterinary Sciences